EDUCOPEDIA, A TOOL TO TEACH GEOGRAPHY - Renata Bernardo Andrade; Ana Claudia Sacramento (Revista on line de Política e Gestão Educacional)
The present work proposal had as objective to analyze how the Educopedia platform referring to the Geography discipline, created in 2010, by the Municipal Department of Education of the City of Rio de Janeiro, can contribute to carry out a geographic education of the elementary school students. The platform is online, contains digital classes in which students and teachers can access self-explanatory activities from anywhere and anytime. The use of new Information and Communication Technologies (ICTs) is growing and can help students develop their cognitive ability to think about concepts, contents and geographic phenomena. As a qualitative research methodology, the content analysis was used, in which the analysis of the page was developed, as well as the general geography contents described. As a result of the preliminary analysis, it is possible to verify the importance of using the platform, as soon as the teacher develops other practices and learning activities during Geography classes.